From the Margins to the Center: Applying Standpoint Theory to Understand and Transform Power Relations in the Classroom - Nurhidayah, Yayah; Humardhiana, Ana; Nurhayati, Eti (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
Constructive and friendly student-lecturer interactions are essential in learning because apart from being able to provide a pleasant educational experience it can also improve students' personal and academic abilities. However, student-lecturer interactions often experience inequality due to the power imbalances among the participants. This study aims to identify the student-lecturer interaction in learning to increase an equal relationship based on students’ perspective. Questionnaires adapted from QTI were distributed to 40 students to collect the data. The results of the study highlight the importance of strong pedagogical leadership and understanding in fostering effective student-lecturer interactions. Students value lecturers who demonstrate leadership, consider their diverse learning needs, and create inclusive learning environments. However, the study also reveals concerns regarding uncertainty and limited student autonomy, consistent with critiques of traditional, lecturer-centered instruction. From a standpoint theory perspective, power imbalances within the classroom can hinder student engagement and motivation and impede the development of crucial 21st-century skills. Cultivating a student-centered environment with open communication, shared decision-making, and student agency is crucial for enhancing the learning experience and fostering student success.